Tailoring Cell Attachment onto Melt Electrowritten Scaffolds via a Phase Separated Hydrogel Coating with Peptide Functionalization - Kelly L. O'Neill; Amanda Kurtz; Ievgenii Liashenko; Guilherme Rocha; Naomi C. Paxton; Paul D. Dalton (Advanced Materials Interfaces)
Abstract Highly porous scaffolds with a high surface area can be designed and fabricated via melt electrowriting (MEW). Here, the study introduces morphological features onto the MEW microfibers via a hydrogel coating of phase‐separated poly(2‐hydroxyethyl methacrylate) (pHEMA). This coating is achieved by capturing phase‐separated droplets of pHEMA onto poly(ε‐caprolactone) (PCL) microfibers via dip‐coating, resulting in a hydrogel coating with webbed structures across pores of the MEW scaffold. Excess pHEMA droplets are removed and phase separation is quenched by washing in water, and then functionalized by dipping the pHEMA coated scaffold into a buffered peptide solution. It is demonstrated that a cysteine‐terminated peptide sequence (Cys‐Gly‐Arg‐Gly‐Asp‐Ser‐Gly (CG‐RGD‐SG)) promotes fibroblast adhesion on the hydrogel‐coated MEW scaffolds compared to unmodified pHEMA and compared to scrambled peptide sequence. Due to the protein‐resistant nature of pHEMA, the hydrogel‐coated scaffolds show less cell attachment than non‐coated PCL scaffolds, while RGD‐functionalized pHEMA scaffolds achieve 2.8‐fold increase in cell attachment (p = 0.02) when compared to non‐functionalized pHEMA. The study therefore presents a platform that combines PCL scaffolds of microscale fibers with a phase‐separated pHEMA hydrogel coating that maintains the high porosity of MEW scaffolds yet increases surface area and, importantly, introduces the capability for tailoring cell attachment via peptide functionalization.